Analysis Of Family Factors, Duration Of Near Work Activities, And Outdoor Activities In Relation To The Degree Of Myopia Among Students At SMPN 1 RAHA In 2025 - Saras Dwianugra; Ika Kartika; Nina Indriyani Nasruddin (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2025)
ABSTRACT Backround. Myopia, or nearsightedness, is a refractive error in which parallel rays of light entering the eye are focused in front of the retina instead of directly on it. This condition is often caused by prolonged near work activities over time. This study aims to identify the factors associated with the degree of myopia among students at SMPN 1 Raha, using samples of students previously diagnosed by a physician or other profesional healthcare. Method. This study employed a quantitative analytic observational method with a cross-sectional approach. Primary data were collected using a questionnaire. A total of 84 respondents were selected using purposive sampling based on inclusion criteria. Data were analyzed using SPSS software with the Chi-Square statistical test. Results. Statistical analysis showed that family history (p = 0.026), prolonged duration of near work activities (>10 hours/day) (p = 0.027), and longer duration of outdoor activities (p = 0.006) were significantly associated with the degree of myopia among students at SMPN 1 Raha. Conclusion. Family history, duration of near work activities, and duration of outdoor activities are factors significantly associated with the degree of myopia in students at SMPN 1 Raha. Keywords. Near Work Activities, Outdoor Activities, Myopia Degree, Family Factors, Junior High School Students.